Salt Stress Reduced the Seedling Growth of Two Larch Species Under Elevated Ozone - Sugai, Tetsuto; Yannan, Wang; Watanabe, Toshihiro; Satoh, Fuyuki; Qu, Laiye; Koike, Takayoshi (Frontiers in Forests and Global Change, 2019)
The effect of elevated ozone (eO3) and soil salinization with alkaline salts in northeastern (NE) China is a serious concern affecting the success of the national replanting project. As planted areas exceed 4 million hectares in China, we must consider future afforestation efforts after thinning and harvesting. Here, we investigated eO3 and salt stress on Dahurian larch (Larix gmelinii var. japonica; DL) and Japanese larch (L. kaempferi; JL) seedlings. The seedlings were exposed to eO3 (~70 nmol mol−1) and ambient ozone (aO3) (~25~40 nmol mol−1) for one growing season in an open top chamber (OTC) system with simulated salinity in NE China (alkaline salt, NaHCO3:NaCl = 9:1, 20mM Na+). The seedlings under salt-free treatment received tap water. Although the effects of eO3 on DL were not significant, eO3 significantly increased total dry mass and total leaf area index of JL. There was no significant reduction in total dry mass under salt stress in both species. The relationship between needle Na and other mineral contents indicated that both species maintained K contents even with excess Na contents in needles. DL showed relatively lower reduction of other mineral contents, indicating higher salt tolerance of needle element homeostasis than JL. Contrary to our hypothesis, there were no interaction effects of eO3 and salt stress on both species. These results indicated that DL seedlings may be more suitable than JL seedlings as a future afforestation species under eO3 levels of <70 nmol mol−1 at saline soil condition.